What Are Visual Illusions?*. (November 2020) - Todorović, Dejan
Visual illusions have been a popular topic of study for a long time, but in recent years, a number of authors have questioned the coherence of this notion. This article deals in depth with ways in which illusions have been, could be, and should be defined and with various criticisms and different conceptions of the notion of illusions. After a review of definitions of illusions in the relevant literature, a more comprehensive but also more restrictive framework is presented, involving both veridicality and illusoriness, and is illustrated using two variants of a 2 × 2 scheme for the presentation of illusions. Many different aspects of illusions are discussed. A set of criteria for illusionhood is listed. Criticisms of the notion of illusions are presented, commented upon, and responded to. Conceptions of illusions differing from the one advocated here are discussed. Throughout the paper, novel variations of illusions are shown, and problems with accounts of some well-known illusions are noted. Examples of strong context effects which are not considered to be illusions are presented. It is concluded that the notion of visual illusions, suitably reformulated, is still viable.